Peningkatan Materi Penelitian Bahasa dan Sastra untuk Dosen Bahasa Indonesia di FKIP Universitas Almuslim oleh Dosen Unsyiah - Yusri Yusuf; Ramli; Mohd. Harun; Razali; Wildan; Saiful (Yayasan Kawanad, 2024)
Improving Language and Literature Research Materials for Indonesian Language Lecturers at FKIP Almuslim University is a collaborative effort carried out by lecturers at the Language and Literature Study Program, FKIP Unsyiah, with their colleagues at FKIP Almuslim. The aim of this community service is to enrich understanding and research skills in the field of Indonesian language and literature among lecturers. Through a series of activities, including workshops, training and interactive discussions, Unsyiah lecturers share experiences, methods and resources to increase the research capacity of Indonesian language lecturers at FKIP Almuslim. It is hoped that this collaboration will make a positive contribution in improving the quality of research and teaching of Indonesian language and literature in the academic environment of FKIP Almuslim University.